Atrophie blanche complicated with lower limb infection and maggot growth: A case report - Zhou, Bo; Qin, Haotian; Huang, Yicong; Wang, Quanzhen; Zhang, Jian; Xiao, Yingfeng; Peng, Yanbin; Yu, Fei (Frontiers in Surgery, 2022)
Background Atrophie blanche (AB) is a thrombotic vascular disease, also known as venous vasculitis or segmental hyaline vasculitis, characterized by chronic recurring painful ulcers on the lower legs, especially the ankles. AB is a clinically rare condition, affecting 1%–5% of the population, specifically middle-aged women with an average age of 45 years, and cases of AB in children are rare. Following recovery, ivory-white atrophy spots accompanied by pigmentation and telangiectasia remain in patients. One of the complications of AB is the parasitic growth of microorganisms infecting the ischemic soft tissue undergoing necrosis in the lower limbs. Furthermore, although infection combined with microbial parasitism is a type of surgical site infection, myiasis is particularly rare, which may warrant limb amputation or may even be life-threatening. Understanding the complications of AB may help in early and timely surgical debridement as well as wound repair. Summarizing the knowledge and treatment strategies of AB and formulating clinical strategies and guidelines for AB management with insights from relevant cases are important. Case summary A 59-year-old woman was hospitalized due to repeated ulceration of the skin of the right lower leg for 3 years, aggravation, and maggot growth for 3 days. In the previous 3 years, the skin and soft tissue of the right calf had become ischemic, necrotic, and infected, but the patient did not seek any medical treatment. Subsequently, 2 years ago, she was diagnosed with AB at the dermatology department of our hospital. After hormone treatment, her right leg improved. However, 1 year ago, the skin and soft tissue of the right leg again became ischemic, necrotic, and infected. This time, the patient did not seek medical treatment and applied musk on her wound. The wound deepened, resulting in the exposure of the tendon and some bones. In addition, a large number of maggots and microorganisms grew in and infested the wound for 3 days before the patient came to our department for treatment. Debridement of the necrotizing infected site on the right lower leg combined with negative pressure vacuum sealing drainage were performed twice within 16 days after admission. Simultaneously, antibiotics were given systemically. On the 17th day after admission, the wound appeared clean, myiasis had resolved, and the growth and coverage of the granulation tissue on the wound were satisfactory. Subsequently, debridement of the infected site on the right leg, removal of skin of the right thigh, and autologous free skin grafting were performed. After 10 days, the wound was clean, all skin grafts had survived, and wound repair was satisfactory. Finally, the patient was discharged after 38 days of hospitalization. Conclusion Although AB is rare, leukodystrophy requires specialized treatment and regular follow-up. If lower limb infection and maggot growth occur simultaneously, self-treatment should be avoided and medical attention must be sought immediately. Early implementation of wound debridement and anti-infective treatment combined with wound repair, which should be performed after cleaning the wound, is advised.